Influence Of Financial Literacy And Lifestyle On Students Financial Management In the Faculty of Economics Department of Accounting Of The Universidade da Paz (UNPAZ) - esus, Herminio da Cruz de J; Daci, Romeu Marques; Silva, Recardina d a (Business Management, 2026)
The Purpose of this research to test and analyze the influence of financial literacy on the financial management of students in the Faculty of Economics, Department of Accounting at the University of Peace (UNPAZ). Research Methods. This research uses a quantitative research type. The population of this study consists of 646 students from the Faculty of Economics, Department of Accounting, at the University of Peace (UNPAZ). The sample used in this research consists of 87 individuals in total. The sampling technique is Slovin sampling. Data technique using a questionnaire and statistical analysis test using multiple linear regression analysis (multiple) and hypothesis testing using _T test. Search Results. The first hypothesis shows that the Financial Literacy variable has a positive and significant influence on Financial Management in the Faculty of Economics, Department of Accounting at the University of Da Paz (UNPAZ). Da Paz (UNPAZ) Results from another research correlation (R) with a value of 0.323 or 32.3%.